STUDI KOORDINASI SISTEM PERALATAN PROTEKSI PADA PENYULANG PIDADA UNTUK MENDAPATKAN SETTING PENGAMAN YANG SELEKTIF - Kadek Adiyaksa Pramana; I.B Gede Manuaba; A.A Gede Maharta Pemayun (Jurnal SPEKTRUM, 2021)
An electric power distribution system must be able to provide electricity to customers. So thatthe company as a provider is required to provide the best for its customers by increasing thereliability of the distribution system. The more customers who use electricity, the greater the possiblefault current, therefore it is necessary to calculate the protection in order to minimize the occurrenceof short circuit disturbances. The protection used on the Pidada feeder is Overcurrent Relay (OCR)and Ground Fault Relay (GFR), this protection relay is used to coordinate current settings inaccordance with applicable standards and can overcome short-circuit fault currents. In this research,a study of the coordination of the Pidada feeder's OCR and GFR settings was conducted using theDigSILENT PowerFactory 15.1.7 application. Calculations were carried out using the zone divisionmethod on the feeder. based on the results of the study, it was found that the Pidada feeder was 0.2s, the Bulu Indah recloser was 0.1 s and the Padang Udayana recloser was 0.02 s. Then on and theground fault relay (GFR) obtained results on the Pidada feeder 0.2 s, Bulu Indah recloser 0.1 s andPadang Udayana recloser 0.08 using standard inverse characteristics. The results of this study arein accordance with the applicable standards, where the standard used is IEC 60255 with a dradingtime of 0.3-0.5 seconds.